Using Storytelling to Improve Listening Skills in Elementary Indonesian Language Learning - Fauji Utami Hutagalung; Yuannisah Aini Nasution; Muhammad Rusli (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
ABSTRACT This study aims to investigate the effectiveness of the storytelling method in enhancing listening skills in Indonesian language learning among Grade V students at SDN 1154. The background of the research stems from the observation that students often struggle to concentrate and understand verbal information during lessons, especially when traditional methods are used. To address this, the study applied the Classroom Action Research (CAR) method consisting of two cycles, each involving planning, implementation, observation, and reflection. The participants were 30 fifth-grade students. Data were gathered through observation, interviews, and listening tests administered before and after the implementation of storytelling. The findings showed significant improvement in students’ listening abilities. In the pre-cycle, only 10 students (33.3%) met the Minimum Mastery Criterion (KKM) of ≥70, with a class average of 61. In Cycle I, the number increased to 19 students (63.3%) achieving mastery, and in Cycle II, all students (100%) reached or exceeded the KKM, with an average score of 75. Additionally, students demonstrated greater enthusiasm and participation in class, suggesting that storytelling not only improved comprehension but also made learning more enjoyable and engaging. The results indicate that the storytelling method is an effective strategy to improve listening skills and can be used to create a more interactive and student-centered learning environment. Its visual and narrative elements help students better grasp language structures, vocabulary, and story content. Implications of this study suggest that educators should integrate storytelling into language instruction to foster stronger listening skills and increase student motivation. This method is especially useful in primary schools where imagination and interest play a vital role in language development. It also serves as a low-cost, adaptable strategy suitable for various classroom settings.